2005
DOI: 10.1002/mus.20411
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose cyclophosphamide in refractory myasthenia gravis with MuSK antibodies

Abstract: We describe a 48-year-old woman with seronegative myasthenia gravis (MG) and high-titer of anti-MuSK antibody. She had severe bulbar and respiratory weakness with minimal limb weakness for 2 years. Her disease responded poorly to all the conventional immunosuppressive regimens. Treatment with immunoablative dose of cyclophosphamide led to dramatic and sustained remission of her symptoms. High-dose cyclophosphamide is an effective alternative in patients with unusually refractory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 22 publications
3
26
0
4
Order By: Relevance
“…Several authors have already reported encouraging anecdotal experience with rituximab, with no serious side effects, good tolerability, and marked clinical improvement in almost all cases [4][5][6][7][8][9][10][11][12]. In fact, we found only one report on a MG patient in whom rituximab was considered inefficacious [15]. However, publication bias may account for this impressive record of rituximab, i.e.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Several authors have already reported encouraging anecdotal experience with rituximab, with no serious side effects, good tolerability, and marked clinical improvement in almost all cases [4][5][6][7][8][9][10][11][12]. In fact, we found only one report on a MG patient in whom rituximab was considered inefficacious [15]. However, publication bias may account for this impressive record of rituximab, i.e.…”
Section: Discussionmentioning
confidence: 64%
“…4-weekly 375 mg/m 2 infusions. Following this, investigators have used different regimens, ranging from no further infusions to a fixed second course of 4-weekly infusions or monthly infusions over two to five months [5,6,8,9,11,15]. Others have used B cell counts during follow-up to guide treatment with rituximab [7,12].…”
Section: Discussionmentioning
confidence: 98%
“…Cyclophosphamide is an alkylating agent, which, given in high doses, rapidly kills lymphocytes and committed hematopoietic progenitors with resultant stem-cell proliferation, immune system reconstitution, and induction of tolerance to pathogenic autoantigens [57,58]. Administration of intravenous pulses of high-dose cyclophosphamide (50 mg/kg of body weight over 1 h for 4 days) in six cases of severe refractory myasthenia gravis [57,58] resulted in clinical improvement by the second month (peaked at 3-12 months), but AChR antibodies or antiMuSK antibodies were not totally eliminated.…”
Section: Cyclophosphamidementioning
confidence: 99%
“…The treatment protocols used in MG have been extrapolated from studies conducted in other autoimmune disorders. Various dosage schedules have been used ranging from a low dose of 2-6 mg/kg to high dose of greater than 1600 mg/m 2 body surface area [18,19]. In lupus nephritis, it has been demonstrated that IV low dose cyclophosphamide is as effective as high dose cyclophosphamide, with the former regimen having fewer associated side effects [4].…”
Section: Discussionmentioning
confidence: 99%